Hematological parameters, and hematopoietic growth factors: EPO and IL-3 in response to whole-body cryostimulation (WBC) in military academy students. - Zbigniew Szygula; Anna Lubkowska; Czesław Giemza; Anna Skrzek; Iwona Bryczkowska; Barbara Dołęgowska (PLoS ONE)
Unlabelled The effects of extreme cold on the human body are not fully understood, there are also no reports on the effect of cryogenic temperatures on the levels of erythropoietin (EPO) and interleukin 3 (IL-3), two important factors that regulate hematopoiesis. Aim determination of changes in peripheral blood cell counts and EPO and IL-3 levels induced by a series of 10, 20 and 30 standard whole-body cryostimulation (WBC) treatments. The study involved 45 men, experimental group (EXP, n = 30) subjected to 30 WBC treatments (-130°C, treatment duration: 3 minutes) and a control group (CON, n = 15). Blood samples were collected before the series of treatments and after 10, 20 and 30 treatments. After 10 and 20 treatments we observed lower red blood cell counts and hematocrit and hemoglobin levels compared to baseline (p<0.05) and the control group (p<0.05). Additionally we observed an increase in hemoglobin concentration in plasma (p<0.05), and bilirubin after 10 and 20 treatments, and a decrease in plasma concentration of haptoglobin after 10, 20 and 30 treatments (p<0.05). The number of leukocytes was higher after 10 and 20 WBC treatments compared to baseline and the CON group. EPO concentration in plasma was elevated and the concentration of IL-3 was lower after 10, 20 and 30 WBC treatments. The decrease in indices of the erythrocytic system, plasma hemoglobin and bilirubin, with a simultaneous decrease in haptoglobin concentrations after 10 and 20 WBC treatments, may be due to increased intravascular hemolysis. At the same time there was a small, but statistically significant increase in the concentration of EPO stimulated erythropoiesis which could facilitate a return of erythrocytic system indices to initial levels after 30 WBC treatments. Changes in the white blood cell system showed transient mobilization of this system under the influence of WBC.